Ketoconazole, an oral antifungal: laboratory and clinical assessment of imidazole drugs. Issue 647 (September 1979) - Borelli, D.; Bran, J. L.; Fuentes, J.; Legendre, R.; Leiderman, E.; Levine, H. B.; Restrepo, A.; Stevens, D. A.
Abstract : Miconazole, a parenterally administered imidazole antifungal agent has been shown to produce responses in systemic fungal infections in man. Ketoconazole, an analogue, can be given by mouth. It is inhibitory in vitro at low concentrations to most fungi. Blood levels after oral administration to animals and man greatly exceed these inhibitory concentrations for several hours. The efficacy of this drug has been demonstrated in animal models. Initial clinical evaluation has produced responses to therapy with 200-400 mg/day in 13 of 16 evaluable patients with systemic and superficial fungal infections, involving 10 fungal pathogens. No toxicity has been noted to date in these human studies. Ketoconazole is a promising agent needing further extensive evaluation.